Identification of Controlled Plant and Development of Its Model by Means of PLC - Roman Fedoryshyn; Sviatoslav Klos; Volodymyr Savytskyi; Oleh Masniak (Energy Engineering and Control Systems)
The results of experimental and theoretical investigation of dynamic and static characteristics of a thermal object (electric oven) as a controlled plant are presented in the paper. The up-to-date microprocessor instruments were applied during the investigation. The experimental study of the plant was made by obtaining the step response curves for the controlling action channel and for the disturbance channel. Fifteen step response curves were recorded during the study. These curves were applied for development of the mathematical model of the plant in the form of static characteristics equations, transfer functions and differential equations. The structure of the model was chosen. The numerical values of the model parameters were calculated. The adequacy of the model was verified. The relative errors of the calculated values of the static characteristics points do not exceed 5 %. The maximum reduced error of the simulated step response curve in comparison to the experimental curve is 7% for the proposed combined method of defining the time constants. The developed model was implemented in a programmable logic controller in order to provide the possibility of studying the automatic control loop with various control laws.